THE EFFECT OF IMPLEMENTING ELECTRONIC WORD WALL MEDIA ON THE VOCABULARY OF FIRST SEMESTER STUDENTS AT SMPN 23 PEKANBARU - Rahmazani, Dhea; Eliwarti, Eliwarti; Maria Safriyanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of using Word Wall media on vocabulary of the first semester students at SMPN 23 Pekanbaru. This research employed a pre-experimental design with a one-group pretest-posttest design. The population of this study was all seventh-grade students of SMPN 23 Pekanbaru in the academic year 2025/2026, consisting of eight parallel classes with approximately 360 students. Cluster random sampling was used to select one class, VII A, which consisted of 40 students as the sample. The instrument used was a multiple-choice vocabulary test consisting of 30 items that had been tested for validity and reliability. The data were analyzed using descriptive statistics, normality test, paired sample t-test, and N-Gain score analysis. The results showed that the average pretest score was 70.63, while the average posttest score increased to 80.90. The paired sample t-test results showed a significance value (2-tailed) of 0.000, which is less than 0.05, indicating a significant difference between students' vocabulary before and after using Word Wall media. Additionally, the N-Gain score analysis resulted in an average of 0.72, which falls into high category. Therefore, it can be concluded that the use of Electronic Word Wall media has a significant effect on improving vocabulary of first semester students at SMPN 23 Pekanbaru.